Synthesis, characterisation of polymer-supported palladium-2-methylimidazole complex catalyst for the hydrogenation of aromatic nitro compounds - Velua, Udayakumar; Stanislaus, Alexander; Virupaiah, Gayathri; Shivakumaraiah; Patil, Kashinath Rangu; Balasubramanian, Viswanathan (Journal of Chemical Research, 2011)
A polymer-supported palladium-2-methylimidazole complex was synthesised and characterised by various physicochemical methods. The complex was successfully used as a catalyst for the hydrogenation of nitrobenzene and a few of its derivatives under ambient conditions. Results reveal that the electronic as well as the steric effects of the substitutent control the rate of hydrogenation of the nitro group in the studied nitro compounds. The kinetics of hydrogenation and the reusability of the catalyst were also studied.
Keywords: aromatic nitro compounds; Hydrogenation; polymer-supported complex catalyst; transition metal complexes